Effectiveness of Flash Card Media To Improve Early Childhood English Letter and Vocabulary Recognition in Reading - Ika Purnama Sari; Rizky Khairunnisa Sormin; Anita Purba; Arum Putri Rahayu; Eri Ester Khairas (Global READ Center, 2023)
This research aims to analyze the effectiveness of Flash Card media to improve early childhood Alphabet and Spelling Vocabulary recognition in reading English at PAUD ADIAN Jaya Karang Sari. This study used qualitative method. The participants in this study were all students of “Class A” PAUD ADIAN Jaya Karang Sari. The result of study on Effectiveness of Flash Card Media to improve the early childhood English Letter and vocabulary recognition in reading English show the implementation of Flash Card. The researchershowed some vocabulary in front of the student by the Flash Card. First, the researcher showed some picture in Flash card, then the researcher mention some vocabulary spell it in the flash card in English. Data was collected by interview and observation sheet. In interview, the researcher invited all the students to mention some vocabulary and student spell it in front of the class. In observation, the researcher makes some quiz about the vocabulary. The researcher showed the flash card. Then make a score for the students that can answer the words and spell it. This research give the implication how to important media learning for early childhood to study English.